Tindak Tutur Direktif Guru pada Kegiatan Mengajar di SLBN 5 Kota Bengkulu - Noveradia, Irsa; Diani, Irma; Rahayu, Ngudining (UNIB Press, 2025)
Directive speech acts play an important role in the learning process, as they are used by teachers to direct, control, and manage students’ responses so that learning objectives can be achieved effectively. This study aims to characterize the directive speech acts used by teachers during learning activities at SLBN 5 Kota Bengkulu. The study focuses on issues related to the use of teachers’ directive speech acts in classroom learning at SLBN 5 Kota Bengkulu. A descriptive method was employed in this research. The study was conducted at SLBN 5 Kota Bengkulu, with data sources consisting of teachers’ directive utterances during Indonesian language learning activities. Data were collected through observation, audio recording, and field notes. Data analysis was carried out through several stages: (1) transcribing oral data into written form, (2) identifying data based on types of directive speech acts, (3) classifying data according to their categories, (4) interpreting the data, and (5) drawing conclusions. The results indicate that teachers’ directive speech acts in Indonesian language learning include (1) requests (requestives), (2) questions (questions), (3) commands (requirements), (4) prohibitions (prohibitives), (5) permissions (permissives), and (6) advice (advisories). In the context of learning at SLBN 5 Kota Bengkulu, these directive speech acts function to direct students’ attention, regulate learning behavior, and assist students in understanding learning instructions in accordance with the needs of students with special needs.